Community members’ experiences training as medical journal reviewers - Cyleste C. Collins; Erika Hood; Jeri Jewett-Tennant; Kurt Stange; Ashwini R. Sehgal (Research Involvement and Engagement, 2023)
Abstract Purpose Although medical research dissemination is intended to benefit members of society, few members of society actually participate in the process of publishing findings. This study shares findings from community members’ (including patients and the public) experiences being trained as medical journal reviewers. Methods We analyzed findings from two focus group interviews of community reviewers (N = 29) to identify themes in their experiences with the training program. Results Community members trained as journal reviewers appreciated learning the context under which manuscript development and review occur from authors and funders, the value of the community member perspectives to science, and strengthened their critical thinking skills. A range of training tools and strategies included glossaries of research terms, creating review guides, practicing reviews, being trained by a supportive team, and working with and learning collaboratively. Conclusions Training as a journal reviewer has a positive impact on participating community members. Programs training community members as journal reviewers should incorporate guest speakers well-versed in community engaged research, group activities, a variety of training tools and materials, and highly supportive training teams.